Plasma Ceramide Species Are Associated with Diabetes Risk in Participants of the Strong Heart Study. Issue 5 (26th October 2019) - Fretts, Amanda M; Jensen, Paul N; Hoofnagle, Andrew; McKnight, Barbara; Howard, Barbara V; Umans, Jason; Yu, Chaoyu; Sitlani, Colleen; Siscovick, David S; King, Irena B; Sotoodehnia, Nona; Lemaitre, Rozenn N
ABSTRACT: Background: Few studies have assessed the associations of ceramides and sphingomyelins (SMs) with diabetes in humans. Objective: We assessed associations of 15 circulating ceramides and SM species with incident diabetes in 2 studies. Methods: The analysis included 435 American-Indian participants from the Strong Heart Study (nested case-control design for analyses; mean age: 57 y; 34% male; median time until diabetes 4.3 y for cases) and 1902 participants from the Strong Heart Family Study (prospective design for analyses; mean age: 37 y; 39% male; median 12.5 y of follow-up). Sphingolipid species were measured using stored plasma samples by sequential LC and MS. Using logistic regression and parametric survival models within studies, and an inverse-variance-weighted meta-analysis across studies, we examined associations of 15 ceramides and SM species with incident diabetes. Results: There were 446 cases of incident diabetes across the studies. Higher circulating concentrations of ceramides containing stearic acid (Cer-18), arachidic acid (Cer-20), and behenic acid (Cer-22) were each associated with a higher risk of diabetes. The RRs for incident diabetes per 1 SD of each log ceramide species (μM) were 1.22 (95% CI: 1.09, 1.37) for Cer-18, 1.18 (95% CI: 1.06, 1.31) for Cer-20, and 1.20 (95% CI: 1.08, 1.32) for Cer-22. Although the magnitude of the risk estimates for the association of ceramides containing lignoceric acid (Cer-24) with diabetes was similar to those for Cer-18, Cer-20, and Cer-22 (RR = 1.13; 95% CI: 1.01, 1.26), the association was not statistically significant after correction for multiple testing ( P = 0.007). Ceramides carrying palmitic acid (Cer-16), SMs, glucosyl-ceramides, or a lactosyl-ceramide were not associated with diabetes risk. Conclusions: Higher concentrations of circulating Cer-18, Cer-20, and Cer-22 were associated with a higher risk of developing diabetes in 2 studies of American-Indian adults. This trial was registered at clinicaltrials.gov as NCT00005134.